The influence of self-awareness as a social beings and mutual respect on strengthening the character of mutual cooperation character of students - Mardiyah, Susi Ainun; Sumardjoko, Bambang; Subowo, Arif (Universitas Tanjungpura, 2025)
This study aims to analyze the influence of self-awareness as a social being and mutual respect towards establishing the character of mutual cooperation of students at MTs Muhammadiyah Blimbing. The research method used is quantitative with a correlational design. The research sample consisted of 146 students selected proportionally from grades VII, VIII, and IX. Data were collected through questionnaires and analyzed using simple linear regression and F-test to test the relationship between variables. The results showed that there was a positive and significant influence between self-awareness as a social being on the character of mutual cooperation with a t-count value of 5.836> t-table 1.977 and a significance of 0.000 < 0.05. In addition to that, mutual respect has a positive and significant effect on the character of mutual cooperation with a t-count value of 9.371> t-table 1.977 and a significance of 0.000 < 0.05. Additionally, with an F-count value of 47.733 > F-table 3.059 and a significance of 0.000 < 0.05, both independent factors significantly contribute to the development of the character of mutual cooperation at the same time. Thus, it can be concluded that increasing self-awareness as a social being and an attitude of mutual respect can strengthen the character of mutual cooperation of students. Therefore, schools need to integrate these values into learning and daily activities in order to build a stronger culture of mutual cooperation